THE IMPORTANCE OF SPIRITUAL VALUES IN THE UPBRINGING OF THE HARMONIOUSLY DEVELOPED PERSON IN TEACHING AND LEARNING PROCESS - Xajieva Iroda, Adambaeva Feruza, Kenjayeva Khurshida , Babadjanova Umida (International Journal of Advanced Science and Technology, 2020)
This article refers to the expression of the idea of a harmoniously developed person in our spiritual values. In spiritual works, attitudes towards a harmoniously developed person are analyzed on the basis of examples and attention is drawn to today's significance.